Bilateral hip septic arthritis caused by nontyphoidal Salmonella group D in a 16-year-old girl with COVID-19: A case report. (June 2022) - Salehi, Mohammadreza; Nourbakhsh, Seyed Mohammad Kazem; Ardakani, Mohammad Vahedian; Abdollahi, Alireza; Khaki, Pegah Afarinesh; Aliramezani, Amir
Abstract: Introduction and importance: Nontyphoidal Salmonella infection can lead to gastroenteritis, enteric fever, and bacteremia. However, joint infections due to this bacterium are rare, and usually associated with immunosuppressive disorders. Case presentation: A 16-year-old girl, with a recent history of acute lymphocytic leukemia (ALL) presented with bacteremia, and bilateral hip pain after COVID-19 symptoms. Clinical presentation, laboratory features and imaging showed bilateral nontyphoidal Salmonella septic arthritis. We administered antibiotics, based on antibiotics susceptibility pattern of the isolated Salmonella . Clinical discussion: The case is presented because reports of bilateral hip joint infection due to nontyphoidal Salmonella are rare especially after COVID-19. When the patient presents with joint discomfort, the clinician should think infection especially in immunocompromised hosts. Conclusion: It illustrates successful management of septic arthritis requires prompt clinical diagnosis, microorganism identification, administration of appropriate systemic antibiotics and hip joint surgery. Highlights: Nontyphoidal Salmonella is one of the most important organisms involved in septic shock and arthritis. Acute lymphocytic leukemia (ALL) is a type of cancer that affects white blood cells (WBC). COVID-19 is a contagious disease caused by severe acute respiratory syndrome coronavirus.